Step-by-step explanation: ummnmm i think 18
F(x) = 5x - 2
f(-3/5) = 5(-3/5) - 2
f(-3/5) = -15/5 - 2
f(-3/5) = -3 - 2
f(-3/5) = -5
Answer:
b (1/15)
Step-by-step explanation:
The area <em>A</em> of a trapezoid with height <em>h</em> and bases <em>b</em>₁ and <em>b</em>₂ is equal to the average of the bases times the height:
<em>A</em> = (<em>b</em>₁ + <em>b</em>₂) <em>h</em> / 2
We're given <em>A</em> = 864, <em>h</em> = 24, and one of the bases has length 30, so
864 = (<em>b</em>₁ + 30) 24 / 2
864 = (<em>b</em>₁ + 30) 12
864 = (<em>b</em>₁ + 30) 12
72 = <em>b</em>₁ + 30
<em>b</em>₁ = 42
Answer:
I am sick
Step-by-step explanation: